High prevalence of abnormalities on CT and MR imaging in children with unilateral sensorineural hearing loss irrespective of age or degree of hearing loss. (June 2017) - van Beeck Calkoen, E.A.; Sanchez Aliaga, E.; Merkus, P.; Smit, C.F.; van de Kamp, J.M.; Mulder, M.F.; Goverts, S.T.; Hensen, E.F.
Abstract: Objective: Evaluation of causal abnormalities identified on CT and MR imaging in children with unilateral sensorineural hearing loss (USNHL), and the association with age and severity of hearing loss. Study design: Retrospective cohort study. Setting: Tertiary referral otology/audiology center. Patients and diagnostic interventions: 102 children diagnosed with USNHL between 2006 and 2016 were included. They underwent CT and/or MR imaging for the evaluation of the etiology of their hearing loss. Main outcome measures: Radiologic abnormalities of the inner ear and brain associated with USNHL. Results: Using CT and/or MR imaging, causal abnormalities were identified in 49%, which is higher than previously reported (25–40%). The most frequently affected site was the labyrinth (29%), followed by the cochlear nerve (9%) and brain (7%). No significant difference in the number or type of abnormalities was found for the degree of hearing loss or age categories. Conclusions: Imaging is essential in the etiologic analysis of USNHL because of the high prevalence of causative abnormalities that can be identified with radiology, irrespective of the patients' age or degree of hearing loss. CT and MR imaging are complementary imaging options. The ideal imaging algorithm is controversial. Based on our findings, we conclude that there is limited additional diagnostic value of simultaneous dual modality imaging over sequential diagnostics. We therefore perform a stepwise radiological workup in order to maximize the diagnostic yield while minimizing impact and costs. If the primary imaging modality does not identify a cause for USNHL, performing the alternative imaging modality should be considered. Level of evidence: Retrospective cohort study 2b